Terahertz Non-destructive testing and imaging of corrosion in coated steel plates. (3rd July 2023) - Jiang, Xuelei; Xu, Ying; Zhao, Dechun
Highlights: The THz technology is proposed to evaluate corrosion in coated steel plates. A method of extracting delay time difference to calculate layer thickness is utilized. The experiments and numerical modeling prove the precision of the THz method. The 3D imaging visualize the geographical distribution of the corrosion thickness. The characteristic thickness values provide a new way to quantify the corrosion. Abstract: The corrosion will lead to the decrease of bearing capacity and durability of steel plate structures. Due to the limitations of the existing non-destructive testing (NDT) approaches, it is difficult to accurately evaluate the corrosion of steel plates, including the corrosion location, area, and thickness. In this paper, a method of extracting the delay time difference in the reflected terahertz (THz) signal is proposed to detect and image the corrosion in coated steel plates. The results from experiments and numerical modeling show that this THz method has a high measurement precision, and the thicknesses of coating and corrosion layers can be measured simultaneously. When the epoxy resin set as coating layer with a thickness of 1000 μm, the minimum thickness of corrosion layer that can be effectively detected in THz model is 25 μm, and the maximum thickness is 3700 μm. Meanwhile, the error percentage of the corrosion layer thickness in the range of 50 ∼ 3700 μm is less than 3%. In addition, a novel imaging technique to visualize the corrosion thickness of steel plates is developed by introducing the THz method. The three-dimensional (3-D) visual imaging directly describes the thickness and location distribution of the corrosion area while removing the effect of the coating layer. Those characteristic values, including the maximum, minimum, average, median, standard deviation, of the corrosion thickness, as well as the ratio of corrosion area/scanning area, can be extracted by this imaging method. In conclusion, the proposed THz technology can realize the NDT of the corrosion area, shape, and thickness, which serves as a guide to quantify the degree of corrosion for steel plate structures.